Ovarian reserve after internal iliac artery ligation. Issue 9 (5th July 2018) - Mathyk, Begum A.; Cetin, Berna A.; Atakul, Nil; Koroglu, Nadiye; Bahat, Pinar Y.; Turan, Gokce; Yuksel, Ilkbal T.
Abstract: Aim: Ligation of major vessels supplying ovaries may alter hormones and ovarian reserve due to disturbances of vascular circulation. Our purpose is to measure serum anti‐Müllerian hormone (AMH) levels and ovarian volume in patients who had internal iliac artery ligation (IIAL) and/or IIAL plus hysterectomy due to uterine atony. Methods: Patients who underwent IIAL and IIAL+ hysterectomy were evaluated 6 months after their operations and were compared with the control group. The hormones, ovarian volume and antral follicle count (AFC) were measured in each group. Results: Serum AMH levels in the post‐partum 6th month interval were lower in the IIAL group than in the control group and were the lowest in the IIAL+ hysterectomy group. Similar to AMH results, AFC and ovarian volumes were also lowest in the IIAL+ hysterectomy group. Conclusion: IIAL and hysterectomy are lifesaving interventions during peripartum hemorrhage; however, they might alter ovarian reserve in the short term.